2012
DOI: 10.1166/jnn.2012.5877
|View full text |Cite
|
Sign up to set email alerts
|

Pt/C Doped TiO<SUB>2</SUB>/SWNTs as Catalyst for Methanol Oxidation

Abstract: Platinum/carbon doped titanium dioxide/single-walled carbon nanotubes (Pt/C/TiO2/SWNTs) were successfully prepared by blending method. These composite catalysts were found to exhibit an anatase TiO2 structure with uniform Pt/C and the existence of SWNTs can be confirmed by transmission electron microscopy (TEM). The composite of Pt/C with TiO2/SWNTs could improve an enhancement in catalytic properties upon applying TiO2/SWNTs as catalyst support. The catalytic oxidation of methanol of Pt/C doped TiO2/SWNTs is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Recently, Pt−C mixed/doped with TiO 2 nanostructures and a TiO 2 −SWCNT composite for methanol oxidation have been studied. 258,259 Xiao et al 259 suggested the importance of high porosity and proton conduction of the TiO 2 cocatalyst. The structural and adsorbed water contents in the cocatalyst also affect oxidation of intermediates during methanol oxidation.…”
Section: Effect Of Tiomentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Pt−C mixed/doped with TiO 2 nanostructures and a TiO 2 −SWCNT composite for methanol oxidation have been studied. 258,259 Xiao et al 259 suggested the importance of high porosity and proton conduction of the TiO 2 cocatalyst. The structural and adsorbed water contents in the cocatalyst also affect oxidation of intermediates during methanol oxidation.…”
Section: Effect Of Tiomentioning
confidence: 99%
“…The high aspect ratio of Pt NWs provides a large surface area of TiO 2 , enabling the bifunctional effect to oxidize CO to CO 2 and thereby releasing Pt active sites. Recently, Pt–C mixed/doped with TiO 2 nanostructures and a TiO 2 –SWCNT composite for methanol oxidation have been studied. , Xiao et al suggested the importance of high porosity and proton conduction of the TiO 2 cocatalyst. The structural and adsorbed water contents in the cocatalyst also affect oxidation of intermediates during methanol oxidation …”
Section: Catalysts Based On Metal Oxide Supportsmentioning
confidence: 99%
“…[21][22][23] Studies of Pt/metal oxide (TiO 2 , CeO 2 , and SnO 2 ) composites have confirmed that the hybrid nanomaterials can exhibit higher catalytic activity and stability during methanol oxidation. [24][25][26][27] Cerium dioxide and cerium dioxide-based nanomaterials can improve catalytic properties and stability by introduction of active metals on their surface. [28] And the introduction of CeO 2 can efficiently oxidize CO ad .…”
Section: Introductionmentioning
confidence: 99%
“…12 The * Author to whom correspondence should be addressed. researchers improved the photocatalytic activity of TiO 2 in the visible light region by doping with metals (Cu, Pt, Fe, Pd, Ag, Ni) 7 8 13-16 and non-metal elements such as nitrogen (N), [17][18][19] boron (B), 20 sulphur (S) 21 and carbon (C) 22 23 on its surface. The another alternative is to combine TiO 2 with semiconductors such as SnO 2 , 24 25 NiO, 26 27 In 2 O 3 , 28 WO 3 , 29 Co 3 O 4 , 30 Fe 2 O 15 3 and Cu 2 O.…”
Section: Introductionmentioning
confidence: 99%